Keeping up with the Queers: White gay and bisexual men's experiences of relationship intimacy and conflict in Cape Town, 1966-2008 - Kleinschmidt, Adam Elliot (Department of Historical Studies, 2022)
Between 1966 and 2008, the social, political and cultural landscape of South Africa changed considerably for queer people living in Cape Town. This thesis intends to explore white gay and bisexual men's experiences of intimacies and conflict in their close relationships during the latter half of apartheid and early democratisation. Interviews and correspondence with eleven men that probed their personal developmental histories, their interactions with social institutions like education and the army, and their intimate relationship histories all revealed information that contributes towards three bodies of literature: firstly, that intersectional histories of race, class and sexuality can be found in social groups that have both privilege and oppression; secondly, that queer identity development is affected by families of origin and social institutions; and thirdly, the queer spaces in Cape Town are reflections of both the queer community and of mainstream heterosexist society. As a result of these findings, it can be stated with conviction that conflict and intimacy in close relationships is an amalgamation of social and personal developments, and that race, class and sexuality have informed the ways in which white queer men perceive themselves and their community. While this research was limited by the small case study size and by minimal archival work, the merits of this case study can be expanded by further oral history projects.